L18 Development of Good Practice of Care, QOL Model's Oriented, for Persons with HD and Complex needs in a Residential Facility. (17th September 2014) - Galli, ML; Corti, S; Chiodelli, G; Cavagnola, R; Fioriti, F; Leoni, M; Uberti, M
Abstract : Background: In Italy, just like in many other countries, there are no long-term care facilities specified for people suffering of Huntington's disease, especially when their needs are represented by severe challenging behaviours which make them impossible to live at home Aims: To answer to needs of people with HD and severe, long lasting, challenging behaviours, we develop and implement a protocol of care QoL oriented to sustain them and their peers in their daily life. Promoting this protocol align the care's management of these people special needs in a residential setting with other very different disabled people. Methods/techniques: Our service consists of a net of 21 residential facilities (different for prevalent support needs: challenging behaviours, high functioning, health needs) with 408 adult subjects with IDD and Autism aged between 18 and 90. Only 6 of them are affected from HD and they don't live in a dedicated setting because their needs are very different. To satisfy the different needs of our population we adopted a QoL model of care (R. Shalock), OMS paradigm of human functioning and we select evidenced based instruments and interventions in a multidisciplinary approach: both a clinical level and a management level. Outcome: The defining specific protocol of care for people with HD supports the clinical decision making process of intervention across lifespan. Conclusions: Developing a good practice of care, QoL oriented, to manage special needs of persons with HD in residential setting, promote interventions person-centred and support patient, family and cares until end of life stages of the disease.